Carotenoids in Aquatic Ecosystems and Aquaculture: A Colorful Business with Implications for Human Health - de Carvalho, Carla C. C. R.; Caramujo, Maria J. (Frontiers in Marine Science, 2017)
The colourful carotenoid pigments are known as biological active compounds that have beneficial effects on the metabolism of animals and humans. Carotenoids provide protection against several stressors, including UV radiation, reactive oxygen species and free radicals, have important roles in vision, and act as precursors of transcription regulators and in the immune system. Studies on human nutrition point to the relevance of consuming functional foods instead of supplementing the human diet with the desired nutrients. This stresses the importance of obtaining dietary items with high quality nutritional value for human consumption. The various biological roles of carotenoids in aquatic animals ascribes them a major role in aquaculture where they are routinely added to ensure the development and health of fish such as salmon, trout and red porgy, and of shellfish like shrimp and lobster. In aquaculture, it is widely recognised that fish larvae dramatically increase their survival rate when reared on live feeds (e.g. rotifers, Artemia sp. and copepods) containing carotenoids. Ultimately, pigmentation provided by carotenoids is one of the relevant quality attributes of the aquatic animal for consumer acceptability and market value. Appropriate feeds for aquaculture are thus required to provide the carotenoids necessary for the desired pigmentation. In this review, we discuss the role of carotenoids in aquatic food webs, both in the wild and in aquaculture, and its relevance for human health.